Efficacy of metribuzin on weeds and yield of fieldpea (Pisum sativum) - Mishra, J S (The Indian Journal of Agricultural Sciences, 2008)
A study was conducted during winter 2004-06 at Jabalpur, to evaluate the efficacy of metribuzin against weeds in fieldpea (Pisum sativum L.) Littleseed canary grass (Phalaris minor Retz.) (37%), wild oats (Avena ludoviciana Dur.) (21%), toothed burclover (Medicago hispida Gaertn.) (38%) and chicory (Cichorium intybus L.) (4%) were the major weeds observed in the field. Application of metribuzin 250 g/ha as post-emergence significantly reduced the population of P. minor but did not control A. ludoviciana compared to its pre-plant soil incorporation and pre-emergence application. Integration of metribuzin with 1 hand-weeding and its sequential application were significantly effective in reducing M.hispida population. Application of metribuzin significantly reduced the root nodulation at 60 days after sowing. Infestation of weeds throughout the crop growth period caused 46% reduction in seed yield of fieldpea. The highest seed yield (2594 kg/ha) was obtained with 2 hand-weeding at 30 and 45 days after sowing, closely followed by metribuzin 250 g/ha at 30 days after sowing + 1 hand weeding at 45 days after sowing (2 331 kg/ha). Sequential application of metribuzin 250 g/ha as pre-emergence + 125 g/ha as post -emergence gave the highest net returns (Rs 11 090) and B:C ratio (1.97).